Evaluasi Penggunaan Obat Antihipertensi pada Pasien Prolanis di Klinik Putra Gemilang Cikampek - Juniarty Mauldi; Wempi Eka Rusmana (Jurnal Health Sains, 2021)
Hypertension is an increase in blood presure from the arteries that is systematic, aka it lasts continuously for a long period of time. Hypertension does not occur seddenly, but through a long process. Uncontrolled high blod pressur for a certain period will cause permanent high blood pressure caled hypertasion. The purpose of this study was determine the characteritics of prolanis patients at the Putra Gemilang Clinic Ckampek. And to determine the percentage of use of antihypertensive drugs in prolanis patients at the Putra Gemilang Clinic Cikampek. This study uses descriptive, quantitative. The data collected in medical records during the study were processed and analyzed descriptive. Furthermore, the required data is recorded and recorded ina worksheet. The population in this study were 67 prolanis patients with a diagnosis of hypertension. The result showed that more famele prolanis patients were diagnosed with hypertansion with a percentage of 46 (68,66%) while 21 (31,34%) men were diagnosed with hypertansion. With age > 60 years as many 44 (65,67%)